The Influence of Job Demands and Job Resources on Employee Performance and Job Satisfaction and Knowledge Sharing as Moderating Variables - Rekma Adi Maheswari, Made (Ekspektra : Jurnal Bisnis dan Manajemen, 2023)
The definition of performance is a description of the level of achievement of the implementation of an activity program or policy in realizing organizational goals, vision and mission goals of the organization which are included through the strategic planning of an organization. This study used a population of 100 employees who had worked at PT Pramana Artha Raharja. The saturated sample technique was used in the research so that the final sample size was 100 respondents. Data analysis in this study used SmartPLS version 3.0. The results in this study of the variables job demands and job resources have no significant effect on job satisfaction, then the variables job demands and job resources have no significant effect on employee performance while the variable job satisfaction has no significant effect on employee performance. Then the knowledge sharing variable has no effect on moderating the relationship between job demands and job resources on employee performance